In vivo ratiometric optical mapping enables high-resolution cardiac electrophysiology in pig models. Issue 11 (7th February 2019) - Lee, Peter; Quintanilla, Jorge G; Alfonso-Almazán, José M; Galán-Arriola, Carlos; Yan, Ping; Sánchez-González, Javier; Pérez-Castellano, Nicasio; Pérez-Villacastín, Julián; Ibañez, Borja; Loew, Leslie M; Filgueiras-Rama, David
Abstract: Aims: Cardiac optical mapping is the gold standard for measuring complex electrophysiology in ex vivo heart preparations. However, new methods for optical mapping in vivo have been elusive. We aimed at developing and validating an experimental method for performing in vivo cardiac optical mapping in pig models. Methods and results: First, we characterized ex vivo the excitation-ratiometric properties during pacing and ventricular fibrillation (VF) of two near-infrared voltage-sensitive dyes (di-4-ANBDQBS/di-4-ANEQ(F)PTEA) optimized for imaging blood-perfused tissue ( n  = 7). Then, optical-fibre recordings in Langendorff-perfused hearts demonstrated that ratiometry permits the recording of optical action potentials (APs) with minimal motion artefacts during contraction ( n  = 7). Ratiometric optical mapping ex vivo also showed that optical AP duration (APD) and conduction velocity (CV) measurements can be accurately obtained to test drug effects. Secondly, we developed a percutaneous dye-loading protocol in vivo to perform high-resolution ratiometric optical mapping of VF dynamics (motion minimal) using a high-speed camera system positioned above the epicardial surface of the exposed heart ( n  = 11). During pacing (motion substantial) we recorded ratiometric optical signals and activation via a 2D fibre array in contact with the epicardial surface ( n  = 7). Optical APs in vivo under general anaesthesia showed significantly faster CV [120 (63–138) cm/s vs. 51 (41–64) cm/s; P  = 0.032] and a statistical trend to longer APD90 [242 (217–254) ms vs. 192 (182–233) ms; P  = 0.095] compared with ex vivo measurements in the contracting heart. The average rate of signal-to-noise ratio (SNR) decay of di-4-ANEQ(F)PTEA in vivo was 0.0671 ± 0.0090 min −1 . However, reloading with di-4-ANEQ(F)PTEA fully recovered the initial SNR. Finally, toxicity studies ( n  = 12) showed that coronary dye injection did not generate systemic nor cardiac damage, although di-4-ANBDQBS injection induced transient hypotension, which was not observed with di-4-ANEQ(F)PTEA. Conclusions: In vivo optical mapping using voltage ratiometry of near-infrared dyes enables high-resolution cardiac electrophysiology in translational pig models. Graphical Abstract: